Safety profile of ramelteon from the perspective of physicians and pharmacists: a 20-year real-world pharmacovigilance analysis based on the FAERS database - Jianhong Wu; Yujie Zhou; Linghe Qiu; Liang Liu; Fei Wang; Lili Zhen; Na Li (BMC Psychiatry)
Abstract Background Ramelteon is the first selective melatonin receptor agonist approved by the FDA, demonstrating significant clinical value in improving sleep latency and sleep quality in patients with insomnia. However, its long-term adverse effects have not been fully evaluated. This study analyzes adverse events associated with ramelteon based on data from the FDA Adverse Event Reporting System (FAERS) database. Methods Case reports submitted by physicians and pharmacists were extracted from the FAERS database from the first quarter of 2005 to the third quarter of 2024. Signal detection was performed using Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-item Gamma Poisson Shrinker (MGPS) algorithms. Results A total of 1,150 reports related to ramelteon were analyzed, covering 26 System Organ Classes (SOC) and 537 preferred terms (PT). The main SOCs included psychiatric disorders, general disorders and administration site conditions, and nervous system disorders. Female patients reported higher instances of insomnia, while hangover, feeling drunk, and decreased blood testosterone were more commonly observed in male patients. At the PT level, hangover, initial insomnia, and glossoptosis exhibited the highest signal strengths. Sleep-related adverse events (AE), such as initial insomnia, somnolence, middle insomnia, poor quality sleep, and hypersomnia, were confirmed. Notably, we report for the first time that ramelteon is associated with parasomnia-related AEs, including sleep talking, sleep terror, screaming, and somnambulism. Conclusion Our study reveals a broad spectrum of AEs associated with ramelteon, including unique sensory experiences (e.g., hangover, derealisation, feeling drunk), reproductive system effects (e.g., decreased libido, priapism), hallucination-related AEs (e.g., visual hallucinations), and rare but clinically significant reactions (e.g., glossoptosis, restless legs syndrome, and photopsia). These findings expand the current understanding of ramelteon’s safety and underscore the importance of closely monitoring patients’ responses during treatment. Emphasis should be placed on individualized treatment strategies and strengthened pharmacovigilance.